Visualizing large trees using the hyperbolic browser - John Lamping; Ramana Rao (CHI'96: Conference companion of the SIGCHI conference on Human Factors in Computing Systems, 1996)
We demonstrate a focus+context (fisheye) scheme for visualizing and manipulating large hierarchies. Our approach is to lay out the hierarchy uniformly on the hyperbolic plane and map this plane onto a circular display region. The projection onto the disk provides a natural mechanism for assigning more space to a portion of the hierarchy while still embedding it in a much larger context. Change of focus is accomplished by translating the structure on the hyperbolic plane, which allows a smooth transition without compromising the presentation of the context.